AB0135 Plasmatic and urinary endothelial microparticles are increased in patients with lupus nephritis. (15th June 2017) - Miranda, F; Barbati, C; Truglia, S; Spinelli, FR; Ceccarelli, F; Alessandri, C; Valesini, G; Conti, F
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease presenting with a wide array of clinical manifestations and incompletely understood pathogenesis. SLE is characterized by alterations in both the innate and adaptive immune system ultimately leading to the loss of immunologic tolerance and occurrence of autoantibodies against nuclear material. Lupus nephritis is one of the most severe features of SLE determining an increase in morbidity e mortality rates. Renal biopsy still represent a fundamental diagnostic and prognostic tool for LN. Therefore, non-invasive surrogate biomarkers of active LN are urgently needed. Circulating, heterogeneous subcellular microparticles (MPs) are released from cells and platelets constitutively and upon cellular activation or apoptosis. Such MPs may reflect the state of their parental cells and tissues, and could serve as markers of pathology. Particularly in SLE, MPs are potential biomarkers and triggers of autoimmunity. Recent studies have demonstrated increased levels of plasmatic EMPs in patients with SLE active disease and their reduction after treatment. Objectives: The aim of this study was to investigate plasmatic and urinary levels of endothelial microparticles in a cohort of SLE patients with and without renal involvement compared to healthy controls. Methods: Consecutive SLE patients and sex- and age-matched HC were included in the study. MPs were isolated from plasma and urine and characterized by flow cytometry using AnxV (a probe that binds to the exposed phosphatidilserine - PS) and antibodies against surface markers endothelial cells (CD31+CD41-). Mann-Whitney and Spearman correlation tests were used. A p value <0.05 was considered statistically significant. Results: Sixty SLE patients (55F:5M, age 41, 7±9.6 Y disease duration 149±112 months) and 29 healthy controls were studied. Twenty-eight patients had renal involvement.The total number of plasmatic MPs was lower in SLE patients than HC (p=0.001). In contrast there was no significant difference in levels of EMPs between the two groups. When the patients were divided according to renal involvement, the patients with active lupus nephritis (A-LN) showed lower plasmatic level of EMPs in comparison to inactive LN (I-LN) (p=0.01), while the patients with I-LN had higher levels of EMPs than HC (p=0.002). There was no significant difference of total urinary level of MPs between SLE patients and HC. Urinary levels of EMPs were higher in SLE and in lupus nephritis patients than HC. Conclusions: The results of the present study show increased urinary and plasmatic levels of EMPs in patients with lupus nephritis in remission. Circulating EMPs have been considered as a potential biomarker of endothelial activation and damage in several autoimmune disorders, and higher EMP levels have been detected in patients with vasculitis and associated with disease activation. According to our results, plasmatic EMPs levels are higher in inactive LN patients than in healthy donors. These results may suggest a potential role of EMP as a biomarker of lupus nephritis Disclosure of Interest: None declared